A Predictive Model for Mortality of Patients with Thalassemia Using Logistic Regression Model and Genetic Algorithm - Hajipour 1, Mahmoud; Etminani 2, Kobra; Rahmatinezhad 2, Zahra; Soltani 3, Maryam; Etemad 4, Koorosh; Eslami 2, Saeid; Golabpour, Amin (Shahroud Journal of Medical Sciences, 2019)
-